Humanizing Pedagogy: The Human-Centric Approach to Technology Integration for Teacher Training - Dhliwayo, Alice; Jita, Thuthukile (Journal of Ecohumanism, 2024)
The rapid expansion of Information and Communication Technologies (ICTs) in education has the potential to revolutionise higher educational opportunities and promote social development for students through techno-equipped teacher educators. However, despite this intensive growth, for Sub-Saharan Africa, a substantial gap still exists between the widespread use of ICTs and their effective implementation in education. In this theoretical paper, we examine the challenges and consequences embedded in this gap in higher education, through the lens of humanising pedagogy, with a focus on the potential harm to the students’ social development. The study however makes some crucial recommendations on policy and practice through an exploration of strategies and propositions for bridging this divide to utilise the full educational potential of ICTs in the African higher education context. We argue for the adoption of humanising pedagogy in higher education for better contribution towards economic and social development through education. We conclude by presenting a suggested model, which we termed ‘Human-centric ICT integration Model’ for effective integration of the said ICTs in a humanistic approach for preservice teacher training.